Development of Go-Bung (Golek Tembung) Application As An Innovation of Android-Based Javanese Vocabulary for Children - Eryneta Nurul Hasanah; Nani Muftihah; Abdul Azis; Cucuk Wawan Budiyanto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
Children of elementary school-age are experiencing obstacles with Javanese vocabulary now. The priority of learning Javanese has declined among children and parents. This is because their attention has shifted to technological developments that have an impact on the high level of gadget usage. This study aimed to: (1) developing Go-Bung (Golek Tembung) as an Android-based application; (2) explain the urgency of Javanese language vocabulary introduction in children; and (3) identify the impact of using the Go-Bung application. The research method used was mixed method. The results obtained were: (1) there were four stages of application development including scenario design, modeling, production, and testing; (2) the importance of introducing Javanese vocabulary to children to revive a sense of cultural love and conserve their culture; and (3) the use of the Go-Bung application had a positive impact on children, parents, and Javanese language teachers. This application can support better quality human resources.Keywords: android application; children; Javanese vocabulary